2020
DOI: 10.21873/cgp.20210
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Kinase Expression Related to Increased Migration of PC-3M Cells Using Global Comparative Phosphoproteome Analysis

Abstract: Background/Aim: Prostate cancer (PCa) is the second-most commonly occurring cancer among men, worldwide. Although the mechanisms associated with the progression of castration-resistant prostate cancer (CRPC) have been widely studied, the mechanism associated with more distant metastases from the bone remains unknown. This study aimed to characterize potential pathogenic kinases associated with highly metastatic PCa, that may regulate phosphorylation in extensively involved and diverse signaling pathways that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Furthermore, kinase inhibitors affect the protein conformation and can have effects beyond inhibition of catalytic activity, and given the importance of interactions of STK10 and SLK for various aspects of cell polarity/shape/migration as well as the additional known substrates of SLK/STK10 such as PLK1, the cellular effects of chemical inhibition of SLK/STK10 cannot be predicted with certainty. Nevertheless, the observations that SLK is essential for breast cancer cell motility, increased SLK expression is associated with increased prostate cancer cell migration, and decreased SLK expression is associated with decreased glomerular epithelial cell migration and decreased fibroblast migration suggested that chemical inhibition would be likely to decrease cell migration. The previous observation that erlotinib, which potently inhibits both SLK and STK10 among many other targets, also decreased glomerular epithelial cell migration further suggested that specific inhibition of SLK/STK10 might decrease cell migration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, kinase inhibitors affect the protein conformation and can have effects beyond inhibition of catalytic activity, and given the importance of interactions of STK10 and SLK for various aspects of cell polarity/shape/migration as well as the additional known substrates of SLK/STK10 such as PLK1, the cellular effects of chemical inhibition of SLK/STK10 cannot be predicted with certainty. Nevertheless, the observations that SLK is essential for breast cancer cell motility, increased SLK expression is associated with increased prostate cancer cell migration, and decreased SLK expression is associated with decreased glomerular epithelial cell migration and decreased fibroblast migration suggested that chemical inhibition would be likely to decrease cell migration. The previous observation that erlotinib, which potently inhibits both SLK and STK10 among many other targets, also decreased glomerular epithelial cell migration further suggested that specific inhibition of SLK/STK10 might decrease cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the observations that SLK is essential for breast cancer cell Table 7. continued motility, 21 increased SLK expression is associated with increased prostate cancer cell migration, 22 and decreased SLK expression is associated with decreased glomerular epithelial cell migration 23 and decreased fibroblast migration 24 suggested that chemical inhibition would be likely to decrease cell migration. The previous observation that erlotinib, which potently inhibits both SLK and STK10 among many other targets, also decreased glomerular epithelial cell migration 23 further suggested that specific inhibition of SLK/STK10 might decrease cell migration.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPKα also phosphorylates p21 Activated Kinase 2 (PAK2) at Ser20 to activate it [118]. PAK2 is repressed by AR signalling, but its level increases during ADT and has been identified as a 'hub' protein for metastasis development [119,120], indicating an oncogenic role for AMPKα in PCa. Knockdown of CAMKK2 reduces transitioning of cells from G1 to S phase of the cell cycle, as CAMKK2 is required for AR-mediated proliferation [121].…”
Section: Cammk2 Signallingmentioning
confidence: 99%
“…To identify the mechanism correlated with more distant metastasis, kinases differentially expressed between the CRPC cell lines PC-3 and PC-3M, which was a metastasis-derived variant of PC-3 cells, were analyzed by MS-based comparative phosphoproteome strategy (95). In this study, 151 phosphoproteins differently expressed between the CRPC cell lines PC-3 and PC-3M were identified (95). Seven motifs, -SP-, -SxxE-, -PxS-, -PxSP-, -SxxK-, -SPxK-, and -SxxxxxP-, were discovered to express a higher level in PC-3M cells compared to PC-3 cells (95).…”
Section: Crpc Invasion and Metastasismentioning
confidence: 99%